2013
DOI: 10.1097/aln.0b013e3182a6b387
|View full text |Cite
|
Sign up to set email alerts
|

Six Percent Hydroxyethyl Starch 130/0.4 (Voluven®) versus 5% Human Serum Albumin for Volume Replacement Therapy during Elective Open-heart Surgery in Pediatric Patients

Abstract: Background: Although 5% albumin (human serum albumin [HSA]) is widely used in cardiac surgery children, synthetic colloids may provide a valuable alternative. This study compared 6% hydroxyethyl starch (HES) 130/0.4 with HSA for volume replacement in this population. Methods: The study was a two-center, randomized, controlled, parallel-group, double-blind trial performed in children aged 2-12 yr undergoing elective surgery for congenital heart disease under extracorporeal circulation. The primary objective was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 20 publications
(17 reference statements)
5
43
0
Order By: Relevance
“…These latter results were confirmed in a meta-analysis (Martin, Jacob et al, 2013). These two formal analyses are in accordance with the results of two prospective randomized controlled studies performed in children undergoing cardiac surgery, that reported the equivalence of tetrastarches compared to human albumin for perioperative fluid replacement, without any increase in the incidence of postoperative complications (Hanart, Khalife et al, 2009;Van der Linden, De Ville et al, 2013). In these studies, the tetrastarch was associated with a decreased fluid balance, which could have a significant impact on postoperative morbidity and mortality (Hassinger, Wald et al, 2014).…”
Section: Levi Department Of Medicine Academic Medical Centre Unisupporting
confidence: 74%
“…These latter results were confirmed in a meta-analysis (Martin, Jacob et al, 2013). These two formal analyses are in accordance with the results of two prospective randomized controlled studies performed in children undergoing cardiac surgery, that reported the equivalence of tetrastarches compared to human albumin for perioperative fluid replacement, without any increase in the incidence of postoperative complications (Hanart, Khalife et al, 2009;Van der Linden, De Ville et al, 2013). In these studies, the tetrastarch was associated with a decreased fluid balance, which could have a significant impact on postoperative morbidity and mortality (Hassinger, Wald et al, 2014).…”
Section: Levi Department Of Medicine Academic Medical Centre Unisupporting
confidence: 74%
“…From a clinical point of view, it should be noted that, in our population, the use of 6% HES 130/0.4 has not been associated with significantly higher perioperative blood loss or other side effects when compared with 4 or 5% albumin. 34,35 In addition, the association between HES 130/0.4 administration and increased perioperative blood loss has recently been contradicted in a review of the literature. 36 In the present study, although the volume of HES 130/0.4 used was higher in the 'bleeders' than in the 'nonbleeders', the volume of HES 130/0.4 was not found to be a predictive factor of postoperative bleeding in multivariate logistic regression analysis.…”
Section: Discussionmentioning
confidence: 97%
“…HES and 5% albumin were used for intraoperative volume replacement including priming of the extracorporeal circuitry. Urinary renal biomarkers (α1-microglobulin, β-N-acetylglucosaminidase, NGAL, and albumin) increased in all patients after surgery but without significant differences between the HES group and 5% albumin group [54]. Van Der Linden et al also showed in a retrospective propensity-matched study that the effectiveness of 6% HES 130/0.4 was equal to that of 4% albumin for kidney injury in 1495 cardiac surgery children with CPB [55].…”
Section: Introductionmentioning
confidence: 99%